Participatory variety selection and promotion of improved faba bean (Vicia faba L.) varieties in the highland areas of North Shewa, Ethiopia - Simegnew Aniley; Yehuala Kassa; Nigussie Kefelegn; Worku Zekargie (Discover Sustainability)
Abstract Faba bean is the most important pulse crop in area coverage and volume of annual production in Ethiopia. However, the productivity in terms of yield is still far below its potential. This research was designed to select and promote the best varieties based on farmers’ preferences. Participatory variety selection was conducted with eight faba bean varieties using a randomized complete block design with three replications. The trial was conducted in the Hagere Mariam District during the 2019 and 2020 main cropping seasons. The result showed that a highly significant variation was observed among the tested varieties in days to flowering (50 to 55.67), thousand seed weight (39.16 to 91.62 g), grain yield (1.88 to 3.03 t ha−1), and percent severity index (11.10% to 30.67%) for faba bean gall disease. A significant difference was also detected in days to maturity (134.67 to 140.67) and plant height (83.27 to 106.57 cm). The highest grain yield was recorded by Hachalu (3.03 t ha−1) followed by Walki (2.92 t ha−1) and Numan (2.86 t ha−1). Farmer’s variety had a lower yield (2.29 t ha−1) by 24.5%, 22.6%, and 18.8% than Hachalu, Walki, and Numan varieties, respectively. Dosha, Numan, and Hachalu have better tolerance to faba bean gall than the farmer’s variety under natural infestation. Among the tested varieties, Walki got a high preference score from farmers based on their selection criteria such as plant height, grain and straw yield, no. of pods/plant and no of seeds/pod, seed size, early maturity, and better adaptability in the area. Consequently, Walki was scaled up and widely disseminated in the region, achieving an average grain yield of 2.64 tons per hectare and a 107.9% yield advantage over the framer’s variety.